2020
DOI: 10.1039/d0nj00583e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and herbicidal application of turpentine derivative p-menthene type secondary amines as sustainable agrochemicals

Abstract: Compound 3a showed excellent herbicidal activity against barnyard grass with IC50 = 7.0 mg L−1, and exhibited good selection for rice, wheat, and radish at 100 mg L−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…p‐ Menth‐3‐enylamine ( 5 ) is a novel monoterpene amine synthesized in very recent years, which can be prepared from N , N '‐diacetyl‐ p ‐menthane‐1,8‐diamines ( 8 ) by two steps as an acid‐catalyzed elimination and alkaline‐catalyzed hydrolysis [20] . Our previous research has successfully synthesized a series of amine derivatives of cis‐ 1,8‐ p ‐menthane‐diamine and p‐ menth‐3‐enylamine and found the secondary amine derivatives ( 6a – 6l , 9a – 9i ), such as N‐ (4‐fluorobenzyl)‐4‐isopropyl‐1‐methylcyclohexane‐3‐enamine ( 6a ), exhibited excellent herbicidal activities toward some noxious weeds [16] . However, it is inevitable to add organic solvents and additives during herbicidal applications because all the above secondary amines are either oily liquid or solid powder with low water solubility.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…p‐ Menth‐3‐enylamine ( 5 ) is a novel monoterpene amine synthesized in very recent years, which can be prepared from N , N '‐diacetyl‐ p ‐menthane‐1,8‐diamines ( 8 ) by two steps as an acid‐catalyzed elimination and alkaline‐catalyzed hydrolysis [20] . Our previous research has successfully synthesized a series of amine derivatives of cis‐ 1,8‐ p ‐menthane‐diamine and p‐ menth‐3‐enylamine and found the secondary amine derivatives ( 6a – 6l , 9a – 9i ), such as N‐ (4‐fluorobenzyl)‐4‐isopropyl‐1‐methylcyclohexane‐3‐enamine ( 6a ), exhibited excellent herbicidal activities toward some noxious weeds [16] . However, it is inevitable to add organic solvents and additives during herbicidal applications because all the above secondary amines are either oily liquid or solid powder with low water solubility.…”
Section: Resultsmentioning
confidence: 99%
“…p ‐Menth‐3‐enylamine, cis‐ 1,8‐ p ‐menthane‐diamine, and p‐ menthene‐7‐amine secondary amines were synthesized from α / β ‐pinene in our laboratory following literature procedures [16,17] . Other chemicals and reagents were commercially available and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proven that secondary amines such as sec-p-menth-3-enylamines and cis-1,8-p-menthane-di-sec-amines exhibit higher herbicidal activities than that of Schiff bases, and they show low toxicity to common crops and mammal cells. 26,27 Perillaldehyde is a natural monoterpene of the p-menthane group originating from plant Perilla frutescens. It was reported that perillaldehyde displayed various bioactivities such as antidepression and antibacterial activity, 28,29 but the herbicidal activity is rarely reported.…”
Section: Introductionmentioning
confidence: 99%